Plant physiological impacts and flavonoid metabolic responses to uptake TiO2 nanoparticles - Kanokporn Sompornpailin; Wilailack Chayaprasert (My University, 2020)
The presence of Titanium dioxide nanoparticles (TiO2 NPs) contamination in the environment is of concern because of their oxidative effect on organisms. Transgenic tobaccos that overexpressed PAP1, a MYB75 gene, were used to investigate the response of plants to the presence of TiO2 NPs and the results were compared to those for wild type (WT) plants. The experiment was performed under tissue culture conditions with daylight fluorescence. The physiological responses of the plants under moderately low concentrations of TiO2 NPs (20–40 mg L-1) were analyzed in relation to metabolic responses and the results were compared to those of plants under zero TiO2 conditions. Under conditions of 20 mg L-1 TiO2, WT and PAP1 plants showed better physiology than plants under other conditions. These plants had higher chlorophyll and carotenoid levels, and better membrane stability than plants under non TiO2 conditions. The WT plants grown in medium at 40 mg L-1 TiO2 showed deteriorated physiology, while PAP1 plants grown under the same condition were shown various changes in physiology depending on the line. Moreover, the content of total soluble sugar (TSS) and flavonoids in the extracts of plant were increased in response to the concentrations of TiO2. However, all PAP1 transgenics had flavone and flavonol contents that were approximately 2–3 times the levels found in WT plants, while TSS and anthocyanin subgroup levels were not different among the WT and transgenic plants. Excessive nanoparticles can induce oxidative damage in cells, and it appears that PAP1 transgenics can alleviate such damage by enhancing flavonoid accumulation.
Keywords: Plant Physiology; Nanoparticles: synthesis and applications